The Influence Of Job Training And Career Development On The Performance Of Police Members (Survey of the Ciamis Resort Police, Traffic Unit) - Awalia, Adisty Aini; Karmila, Mila; Sutrisna, Arga (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This research aims to determine the effect of Job Training and Career Development on the Performance of Police Members at the Ciamis Resort Police. The method used is a case study, data was obtained through questionnaires to members of the National Police at Ciamis Police. Sampling used a random sampling technique, using the Slovin formula and the analysis method used was the multiple linear regression analysis method. The research results show that job training, career development and performance are included in the Very Good classification. Simultaneously, job training and career development have a significant effect on the performance of members of the Ciamis Resort Police. Partially, job training and career development variables have a significant effect on the performance of members of the Ciamis Resort Police.